Radio-Frequency Optically Pumped Magnetometers for Eddy Current Measurements - Rushton, Lucas Martin (2023)
Radio-frequency optically pumped magnetometers (RF OPMs) are capable of measuring oscillating magnetic fields with high sensitivity in the fT/sqrt(Hz) range. Two types of RF OPMs are presented in this thesis. The first is a portable, orientation-based RF OPM with 600 fT/sqrt(Hz) sensitivity at 10 kHz in unshielded conditions, a new benchmark for a portable unshielded RF OPM, and 200 fT/sqrt(Hz) sensitivity at 10 kHz in shielded conditions, close to the spin projection noise limit. Eddy current measurements were performed with this OPM to remotely detect aluminium disks with diameters as small as 1.5 cm at distances of ~25 cm from both the excitation coil and the OPM, demonstrating the possibility of using OPMs for remote sensing. Off-axis measurements were performed with this OPM to illustrate how the OPM readout can be interpreted for remote sensing. All aspects of the theory, experimental setup and results relevant for this orientation-based RF OPM and eddy current measurements are presented in this thesis.